Perbedaan Teknik Ekstraksi dan Pengaruhnya terhadap Aktivitas Biologis serta Hasil Senyawa Fitokimia pada Bahan Alam - Eprariana, Eprariana; Fiona Maulidia; Siti Nor Adidah; Chiena Nazerina Yoshi; Raida Raida; Gina Norhalija; Della Puspita (Jurnal Pendidikan Kimia, Fisika dan Biologi, 2025)
This study aims to analyze the differences in various extraction techniques and their relationship to the yield and biological activity of phytochemical compounds from natural materials. The research was conducted through a systematic literature review from various reliable scientific sources over the last decade. The results indicate that extraction methods such as maceration, soxhlet extraction, microwave-assisted extraction (MAE), and ultrasound-assisted extraction (UAE) have varying effectiveness. The effectiveness of these methods is highly dependent on the type of material, solvent used, and process parameters such as temperature, time, and solvent-to-material ratio. Modern extraction methods such as sonication, MAE, and UAE tend to produce higher yields and better biological activity. These modern methods have the advantage of being more time-efficient and requiring fewer solvents, thus allowing the extraction of active compounds more optimally. Additionally, technologies like microwave and ultrasonic waves help break down the cell walls of natural materials, enhancing the release of phytochemical compounds more effectively and rapidly. However, conventional methods such as maceration and soxhlet extraction remain relevant, especially for materials containing thermolabile compounds that may degrade at high temperatures. These methods are still preferred to maintain the stability of active compounds sensitive to thermal degradation. Choosing the appropriate extraction method is crucial in producing high-quality extracts that can potentially be used as raw materials for phytopharmaceuticals, supplements, or other natural products. This study provides a strong theoretical foundation for further experimental research and guidance in selecting extraction methods based on the required efficiency and effectiveness for industrial applications. Thus, this study contributes to the development of more efficient and high-quality natural products.